Health-related consequences of caring for dependent relatives in older adult caregivers - Nildete Pereira Gomes; Larissa Chaves Pedreira; Nadirlene Pereira Gomes; Elaine de Oliveira Souza Fonseca; Luciana Araújo dos Reis; Alice de Andrade Santos (SciELO, 2019)
ABSTRACT Objective: To know the health-related consequences of caring for dependent relatives in older adult caregivers. Method: Qualitative research carried out with older adult women who cared for family members enrolled in a federal public home care program. The identification of the older adult caregivers was done by consulting the patient's charts, and the interview took place from March to June 2017. The data were systematized based on Content Analysis. Results: Six older adult caregivers of people with impaired functional capacity participated in the study. Three categories emerged: care-related musculoskeletal pain; health problems related to the somatization of the lived feeling; and self-care deficit by virtue of caring for another. Conclusion: The study revealed the consequences of caring for dependent family members on the health of older adult caregivers. Careful management is essential to prevent and/or reduce health problems, especially regarding the musculoskeletal system.